Branched late-steps of the cytosolic iron-sulphur cluster assembly machinery of Trypanosoma brucei - Tonini, Maiko Luis; Peña-Diaz, Priscila; Haindrich, Alexander C; Basu, Somsuvro; Kriegová, Eva; Pierik, Antonio J; Lill, Roland; MacNeill, Stuart A; Smith, Terry K; Lukeš, Julius (PLoS pathogens, 2018)
Fe-S clusters are ubiquitous cofactors of proteins involved in a variety of essential cellular processes. The biogenesis of Fe-S clusters in the cytosol and their insertion into proteins is accomplished through the cytosolic iron-sulphur protein assembly (CIA) machinery. The early- and middle-acting modules of the CIA pathway concerned with the assembly and trafficking of Fe-S clusters have been previously characterised in the parasitic protist Trypanosoma brucei. In this study, we applied proteomic and genetic approaches to gain insights into the network of protein-protein interactions of the late-acting CIA targeting complex in T. brucei. All components of the canonical CIA machinery are present in T. brucei including, as in humans, two distinct CIA2 homologues TbCIA2A and TbCIA2B. These two proteins are found interacting with TbCIA1, yet the interaction is mutually exclusive, as determined by mass spectrometry. Ablation of most of the components of the CIA targeting complex by RNAi led to impaired cell growth in vitro, with the exception of TbCIA2A in procyclic form (PCF) trypanosomes. Depletion of the CIA-targeting complex was accompanied by reduced levels of protein-bound cytosolic iron and decreased activity of an Fe-S dependent enzyme in PCF trypanosomes. We demonstrate that the C-terminal domain of TbMMS19 acts as a docking site for TbCIA2B and TbCIA1, forming a trimeric complex that also interacts with target Fe-S apo-proteins and the middle-acting CIA component TbNAR1.
Keywords: Trypanosomiasis; interakční proteinové domény a motivy; trypanozomiáza; myši inbrední BALB C; cytosol; protozoální proteiny; Iron-Sulfur Proteins; Trypanosoma brucei brucei; Cytosol; Mice, Inbred BALB C; Protein Interaction Domains and Motifs; proteiny obsahující železo a síru; Animals; ženské pohlaví; konformace proteinů; zvířata; myši; Protein Conformation; Protozoan Proteins; Mice; Female